1997
DOI: 10.2503/jjshs.65.753
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Fruit Cracking and Changes of Fruit Diameter Associated with Solute Flow to Fruit in Cherry Tomatoes

Abstract: SummaryThe course of cracking in cherry tomato (Lycopersicon esculentum Mill.) grown in water culture in a glasshouse in relation to the diurnal changes in fruit size and the rate of solute uptake was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 12 publications
0
13
0
4
Order By: Relevance
“…In an uniaxiale tensile test the isolated CM is subjected to constant strain rates at defi ned stages of hydration. In vivo, however, the CM is part of the exocarp composite and subjected to biaxiale strain during fruit growth, where strain rates are markedly lower than in tensile tests and often subjected to diurnal oscillations (Ohta et al, 1997). Our data demonstrate that the structural support of the CM by underlying epidermal and hypodermal cell layers is indeed important (Figs.…”
Section: Effect Of Water On Mechanical Properties Of CMmentioning
confidence: 71%
“…In an uniaxiale tensile test the isolated CM is subjected to constant strain rates at defi ned stages of hydration. In vivo, however, the CM is part of the exocarp composite and subjected to biaxiale strain during fruit growth, where strain rates are markedly lower than in tensile tests and often subjected to diurnal oscillations (Ohta et al, 1997). Our data demonstrate that the structural support of the CM by underlying epidermal and hypodermal cell layers is indeed important (Figs.…”
Section: Effect Of Water On Mechanical Properties Of CMmentioning
confidence: 71%
“…Since new synthesis of CM material was essentially absent in the sweet cherry fruit during stage III, S and the resulting stress were positively related to R. Also, the frequency of exocarp segments having microscopic cracks increased markedly during the period of high S. Surface disorders are common in a number of fruit crops that (i) may be directly or indirectly related to CM failure and (ii) are induced during developmental stages where R and S are high. Such disorders include russeting in apple (Faust and Shear 1972) and prune (Michailides 1991), russeting (Bakker 1988) and cracking in tomato (Ohta et al 1997), and maturity bronzing of banana (Williams et al 1989(Williams et al , 1990. Also, the characteristic cork net of muskmelon is thought to originate from cuticular ®ssures and subsequent formation of a periderm (Webster and Craig 1976).…”
Section: Physiological Implicationsmentioning
confidence: 97%
“…Cracking can occur during fruit growth and/or ripening and affects several fruits such as tomato, pepper, cherries and many others (Sekse 1995, Aloni et al 1998, Dorais et al 2004, Huang et al 2006). Cracks are assumed to occur when internal pressure exceeds the breaking stress of the epidermis, mainly the cuticle (Ohta et al 1997). In cherry tomato, cracking only appears during ripening (Bakker 1988, Ehret et al 1993) and has been shown to have a genetic as well as an environmental component (Peet 1992).…”
Section: Introductionmentioning
confidence: 99%